The role of psychological factors in predicting latrine ownership and consistent latrine use in rural Ethiopia: a cross-sectional study - Fikralem Alemu; Abera Kumie; Girmay Medhin; Janvier Gasana (BMC, 2018)
Abstract Background Inadequate sanitation is one of the leading causes of disease in poor and middle-income countries. Objective The objective of the study was to identify the psychological factors that predict latrine ownership and consistent latrine use in the rural Becho district of central Ethiopia. Method A quantitative, cross-sectional, community based study was conducted. A total of 1047 heads of household were interviewed using a structured questionnaire. Ownership of latrine and consistent latrine use constituted the outcome variable of the study. Data were entered using Epi Info version 3.5.4 and were analyzed using SPSS version 20. Results Of the 1047 households, 73% owned a traditional pit latrine. Among the psychological factors, attitude (AOR 1.70; 95% CI 1.21-2.37) and injunctive norm (AOR 6.18; 95% CI 4.46-10.44) were positively and significantly associated with latrine ownership. Among the demographic factors, having a family size of more than six (AOR = 1.43; 95% CI 1.01-1.97, having a child attending school (AOR = 1.88; 95% CI 1.17-3.02), and having a high school education (AOR = 1.98; 95% CI 1.34-2.87) were significantly associated with latrine ownership. With respect to exposure to communication about sanitation (the cues to action), households that had a family member who took part in Community Led Total Sanitation and Hygiene (CLTSH) triggering were three times more likely to be latrine owners than those who did not participate in CLTSH triggering (95% CI 1.92-4.78.) Results from adjusted logistic regression analysis of potential predictors of consistent latrine use showed that having a positive attitude (AOR 7.00; 95% CI 4.55-10.55), owning of a latrine that had superstructure (AOR 2.3 95% CI 1.47-3.48), having a clean latrine (AOR 1.69 95% CI 1.00-3.00), and having a latrine with a protected door (AOR 1.94; 95% CI 1.10-3.48) were significantly associated with consistent latrine use. Conclusion The study findings showed that attitude and injunctive norm are the psychological predictors of latrine ownership, and consistent latrine use was associated with attitude, cleanliness of the latrine, and its privacy. Hence, sanitation intervention needs to focus on changing societal norms, attitudes, and the promotion of latrine quality.